Design and analysis of the cable-driven parallel robot for cleaning exterior wall of buildings. (8th February 2021) - Shao, Zhufeng; Xie, Guangqiang; Zhang, Zhaokun; Wang, Liping
With the development of cities, more high-rise buildings continue to emerge. Regular cleaning of building exterior walls is necessary, which mainly relies on manual work now. In this article, the planar four-cable-driven parallel robot (CDPR) is adopted to carry out the external cleaning of high-rise buildings. Firstly, the kinematic model and static model are established. The influence of the maximum cable force on the workspace is analyzed, and the position of the cable connection points on the end effector is discussed. Then, the stiffness of the CDPR is analyzed, which reveals that a large difference of the width-to-height ratio between the end effector and the base improves the stiffness condition number and average stiffness of the CDPR. Considering the size of the cleaning module, the horizontal cross layout is adopted and cable connection points are determined. The cable force range is discussed considering the variable size of the base. Finally, the prototype of a cable-driven cleaning robot is designed accordingly.